2002
DOI: 10.1038/sj.bjc.6600459
|View full text |Cite
|
Sign up to set email alerts
|

Antisense inhibition of methylenetetrahydrofolate reductase reduces survival of methionine-dependent tumour lines

Abstract: Transformed cells have been documented to be methionine-dependent, suggesting that inhibition of methionine synthesis might be useful for cancer therapy. Methylenetetrahydrofolate reductase synthesises 5-methyltetrahydrofolate, the methyl donor utilised in methionine synthesis from homocysteine by vitamin B 12 -dependent methionine synthase. We hypothesised that methylenetetrahydrofolate reductase inhibition would affect cell viability through decreased methionine synthesis. Using medium lacking methionine, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…These include A498 (renal), PC-3 (prostate), MCF7 (breast), SW-620 (colon), HL-60 (leukemia), K-562 (leukemia), and A549 (non-small cell lung carcinoma; refs. 3,27,28,30). MS and MSR were expressed in all seven of these cell lines at levels that were comparable to those in other cell lines originating from the same tissue.…”
Section: Resultsmentioning
confidence: 62%
“…These include A498 (renal), PC-3 (prostate), MCF7 (breast), SW-620 (colon), HL-60 (leukemia), K-562 (leukemia), and A549 (non-small cell lung carcinoma; refs. 3,27,28,30). MS and MSR were expressed in all seven of these cell lines at levels that were comparable to those in other cell lines originating from the same tissue.…”
Section: Resultsmentioning
confidence: 62%
“…Previous studies in our laboratory with MTHFR antisense resulted in significant reductions of MTHFR protein that affected survival of methionine-dependent cancer cell lines, whereas nontransformed cells (human diploid fibroblasts) were not affected. EX5 of the human MTHFR mRNA was determined to be quite effective and examined in this study, although an antisense against exon 4 also had growth inhibitory properties (12).…”
Section: Discussionmentioning
confidence: 99%
“…The EX5 MTHFR specific antisense (EX5; sequence 5V -AGC TGC CGA AGG GAG TGG TA-3V) targets nucleotides 796 to 815 in exon 5 of the human MTHFR mRNA. Selection of EX5 was based on the results of our previous work (12). The control scrambled antisense oligodeoxynucleotide (CTS; sequence 5V -TGT TGA CAA AAG GAG TGG TG-3V) has the same base composition in random order.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…51 In addition to c-myc, 52 other genes relevant to breast cancer have been successfully targeted by antisense oligonucleotides such as aV integrin, 53 ribosomal protein P2, 54 c-erbB-2, 55 methylenetetrahydrofolate reductase (MTHFR), 56 p21, 57 protein kinase C-alpha (PKC-a), 58,59 Bcl-2, 60 telomerase reverse transcriptase and telomerase, 61 plasma membrane calcium ATPase, 62 type I insulin-like growth factor receptor (IGF-IR), 63 and c-fos. 52 Compared with preclinical studies, far fewer clinical studies of oligonucleotides have been reported.…”
Section: Mutation Compensationmentioning
confidence: 99%